Exploring Parent–Child Conversations about Live Snakes and Spiders: Implications for the Development of Animal Fears. Issue 1 (17th December 2020) - Conrad, Megan; Reider, Lori B.; LoBue, Vanessa
Abstract: Snakes and spiders commonly elicit fear. However, despite the pervasiveness of these fears in adulthood, little is known about how they develop in early childhood. Informal learning environments, like zoos, allow for observation of parent–child conversations about these animals. Such naturalistic conversations may contain negative talk and may be one mechanism for the development of fears. In Study 1, we interviewed 241 preschool-aged children about snakes and spiders. In Study 2, 15 parent–child conversations were observed at a zoo. Across studies, we found that participants provided less positive (Study 2) and more negative (Study 1) information about snakes and spiders than other animals, and that children reported more fear (Study 1). Our results highlight the availability of negative information about snakes and spiders, and we discuss how we can use children's early experiences in informal learning settings to teach them about animals without contributing to the development of early fears.